2021
DOI: 10.1177/0886260521991895
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Violent Discipline at Home and Risk of Illness and Injury in Children: Findings From a Cross-sectional Study in Rural Western China

Abstract: To estimate the prevalence of violent discipline at home against young children, and to explore the potential association between violent discipline at home and multifaceted health risks in children. A community-based cross-sectional survey was conducted in twenty rural counties of weight provinces in western China. The information about child neglect and socio-demographic factors, exposure to different forms of violent discipline at home and four health outcomes was collected by face-to-face interview. Before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 55 publications
(64 reference statements)
0
5
0
Order By: Relevance
“…Anthropometric and hemoglobin measures of the child were also collected during the fieldwork. Details of this survey have been described in previous studies [ 23 , 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Anthropometric and hemoglobin measures of the child were also collected during the fieldwork. Details of this survey have been described in previous studies [ 23 , 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, the prevalence of total violent discipline was as high as 72.7%, 59.3% for psychological aggression, and 60.4% for physical punishment for left-behind children under 6 years of age. Huang Y. et al reported a higher prevalence of violent discipline (76.4%), physical punishment (68.3%), and a similar prevalence of psychological aggression (57.5%) in rural western China [ 14 ]. Another study found similar results in rural counties of China [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Left-behind children were more likely to suffer from psychological aggression and physical punishment compared with non-left-behind children [ 13 ]. Approximately 73.1% of left-behind children in China reported experiencing violent discipline [ 14 ]. Currently, only a few studies have investigated the prevalence of violent discipline among left-behind children in rural areas of China [ 14 , 15 ], which mainly focused on children under 4 years old.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Authoritarian parenting styles make children obedient to the values set by their parents, with a tendency to restrict their desires and often impose physical punishment on them if they fail to meet the standards set by their parents (Lisnadiyanti & Bagus, 2019). Families in rural Western China, for instance, use severe physical punishment to discipline their children at home, posing a health risk to them (Huang et al, 2022). Conversely, permissive parenting styles may result in violence in schools since children become accustomed to acting freely without parental supervision or discipline, which may encourage bullying (Lisnadiyanti & Bagus, 2019).…”
Section: Individual Factorsmentioning
confidence: 99%